Papua New Guinea - Fox, Mary Virginia (Chicago : Childrens Press, 1994)
Discusses the geography, history, government, people, and culture of this southeast Asian country.
Includes index.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
7.6
4-6
Keywords: Papua New Guinea -- Juvenile literature; Papua New Guinea; Papua New Guinea